Factors Influencing User Satisfaction with Mobile Applications for Promoting Thai Community Products - Pislae-ngam, Kattakamon; Inmor, Sureerut; Pukrongta, Nisit (Journal of Applied Data Sciences, 2024)
This study investigates key factors affecting user satisfaction with mobile applications like Shopee, Lazada, and TikTok Shop, focusing on promoting community products in Pathum Thani Province, Thailand. As mobile applications gain significance for marketing local goods, the research aims to explore how various features influence satisfaction and trust among users. The study collected data from 400 local entrepreneurs between January and March 2024, all experienced in using mobile apps to sell products. A confirmatory factor analysis (CFA) was conducted to examine five critical factors: requirements, accessibility, accuracy, security, and trust. The findings indicate that accuracy (β = 0.75) and accessibility (β = 0.71) significantly impact user satisfaction, emphasizing the importance of precise content and ease of use. Additionally, security (β = 0.76) and trust (β = 0.72) play crucial roles in maintaining user confidence in app transactions. All model indicators were validated at the 0.01 significance level, indicating a good fit for the hypothesized relationships between factors. The study’s novelty lies in highlighting specific app features that enhance user experiences in promoting local products. By focusing on the essential aspects of mobile app functionality, this research provides valuable insights to developers and local businesses for creating effective platforms, ultimately supporting sustainable economic growth.